Functional Role of p21 During the Cellular Response to Stress - Gorospe, Myriam (Gene Expr, 2018)
A wide range of stress stimuli, including oxidants, genotoxins, metabolic deficiencies, and irradiation, have been shown to induce expression of the cyclin-dependent kinase inhibitor p21. Among the best characterized mediators of p21 induction by stress is the tumor suppressor gene p53, which acts as a transcriptional activator to enhance the expression of the p21 gene. However, many other mechanisms involving transcriptional and posttranscriptional events have been found to participate in the elevation of p21 levels by stressful agents. The significance of the stress-mediated elevation in p21 expression is not fully understood, but it is clear that alterations in p21 expression impact on the ability of the cell to survive the insult. Although a large number of reports have demonstrated correlations between the expression of p21 and cellular outcome, this review will focus only on those reports where the role of p21 in a given stress paradigm has been investigated directly, through use of different strategies to manipulate p21 expression followed by assessment of the consequences of altered p21 expression on cell survival. The majority of such studies have revealed that p21 exerts a protective function against stress, and this property appears to rely, at least in part, on the ability of p21 to suppress cell proliferation. A few exceptions to this universal protective influence of p21 have also been observed and will be discussed.